CATALYSIS OF TRIVALENT PHOSPHORUS COMPOUNDS OF THE REACTIONS OF SUBSTITUTED BENZOIC ACIDS WITH ANILINE - Shteinberg, Leon (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2022)
The catalytic preparation of substituted benzanilides by the reaction of substituted benzoic acids with aniline is an important model process that has been intensively developed recently, in the field of the «green chemistry» concept, direct catalytic amidation, and its study is an urgent scientific and practical task. Within the framework of solving this problem, the catalysis of the acylation of aniline by substituted benzoic acids with trivalent phosphorus compounds P(III) was studied. It was established that P(III) in the amount of only 2% mol. from substituted benzoic acid effectively catalyze this reaction, which proceeds in boiling low-polar solvents with intensive water distillation in an air atmosphere, which leads to obtaining anilides of substituted benzoic acids with a yield close to quantitative. The new catalysts, phosphorus trichloride and tribromide, phosphorous acid, successfully complement the catalytic system tetrabutoxytitanate/polybutoxytitanate, previously used for these purposes, allowing to obtain anilides of aminobenzoic acids with greater selectivity, as well as anilides of oxybenzoic acids. The study of the kinetic regularities of the reaction catalyzed by phosphorus trichloride showed a weak effect of substituents: |ρ| ≤ 0.61. Hammett dependences are represented by curves with a maximum, straight line segments are characteristic only for certain groups of substituents, both for meta- and para-substituted and for orthosubstituted benzoic acids. One of the possible mechanisms of acylation is the formation in situ in the first minutes of the reaction of aniline phosphite, which can act as an oxygen-nucleophilic catalyst, and, upon interaction with substituted benzoic acid, forms the corresponding benzoyl phosphite, which is then attacked by a free aniline molecule to obtain substituted benzanilide. The ortho effect for P(III) catalysis is absent or very weak, in the case of aminobenzoic acids. At the same time, anthranilic acid can form a phosphite with phosphorous acid, which directly participates in catalysis.